(untitled) (Fiep Bulletin - online, 2014)
Fibromyalgia is a chronic pathology of unknown etiology that causes generalized pain, sleep disorders, head-aches, memory, concentration and mood disorders, irritable bowel syndrome, and fatigue. Recent studies suggest that aerobic physical activity is being used as a form of treatment for fibromyalgia, with the objective of improving health and physical aptitude of patients, however, the effectiveness of these treatment in positively changing the symptoms related to fibromyalgia remain unclear. The goal of this review was to identify the effects of different aerobic physical activity programs in patients with fibromyalgia in relation to pain, depression, fatigue, functionality, physical aptitude, quality of life, Fibromyalgia impact and general health status. The articles were searched in the PubMed database. The key-words used were: Fibromyalgia AND Aerobic Exercise (all fields). The article types selected were: Articles types - Clinical Trial, Controlled clinical Trial, Randomized Clinical Trial e Meta-Analysis; Text Availability - Full Text Available; Publication Dates - 5 years; Species - Human; Languages – English. Sixty six articles were found and after a thorough reading, 12 were selected. The main results that showed statistical significance were physical aptitude, functionality, and general health status. There was no consensus in regards to the other aspects analyzed.